The Effectiveness of Ropivacaine and Mepivacaine in the Postoperative Pain after Third Lower Molar Surgery - Crincoli, Vito (Int J Med Sci, 2015)
Aim: To compare the efficacy of 0.75% ropivacaine with 3% mepivacaine for pain control in the first 24 hours after surgical removal of lower third molars, using a quantitative measurement such as VAS. The secondary objective involved rescue analgesia. Methods: Forty-five patients, 21 females and 24 males, mean age 23,2 ± 3 years, underwent surgical removal of third molars in two separate sessions. A split-mouth design was chosen, so each patient underwent both the first and second surgeries, having for each extraction a different anesthetic. The second extraction was carried out 1 month later. Parameters evaluated were: onset of anesthesia, duration of surgery, lip numbness, timing of pain appearance and first analgesic intake. Results: No significant differences about onset of anesthesia, duration of surgical procedures, and timing of first analgesic intake were found. Lower lip numbness, on the other hand, was more prolonged after using ropivacaine (p < 0.0001) and the onset of postoperative pain was more delayed after anesthesia with ropivacaine (p=0.0048). Pain scores at 1 and 2 hours after surgery were 3.5 ± 2.0 and 4.1 ±1.3 after injection of mepivacaine, and 2.7 ±2.2 and 2.9 ±2.4 after ropivacaine (p value =0.006 for both time points). No significant differences in pain score were recorded between the two anesthetics at 12 and 24 hours post surgery. Conclusions: With the use of ropivacaine, the discomfort caused by prolonged lip numbness is counterbalanced by less postoperative discomfort after surgery. In addition, when compared with other long-acting anesthetics, ropivacaine ensures a safer anesthetic profile for medically complex patients.